O05.2 Measuring Syphilis: Quantitative PCR Can Be Used to Monitor Treatment Response. (13th July 2013) - Tipple, C; Hodson, L; Jones, R; Rayment, M; Nwokolo, N; McClure, M; Taylor, G
Abstract : Background: The humoral response to Treponema pallidum ( T. pallidum ), which causes syphilis, is divided into 'non-specific' anti-lipid and specific anti-treponemal protein antibodies. A four-fold reduction in anti-lipid antibodies is used to diagnose cure, which can take six or more months. Quantitative PCR (qPCR) can measure T. pallidum DNA copies in blood and ulcer samples. Bacteraemia is more common and of higher load in early disease. We present a pilot study monitoring the early treatment response in patients with infectious syphilis by qPCR. Methods: Patients with symptomatic primary or secondary disease were admitted to hospital and following baseline sampling were treated with 2.4 M units of benzathine penicillin. Whole blood was collected into EDTA and Tempus RNA preservation tubes and the ulcer sampled using a philtre paper strip every four hours for T. pallidum DNA ( tpp047 gene) and RNA ( 16S rRNA ) quantification. Sampling ended when two consecutive PCRs were negative. Standard serological follow-up was performed. Results: Three men were recruited (two secondary, one primary). All were homosexual and two were HIV-1 infected. Blood DNA quantification and clearance: A mean peak-level of 1611(range 1212) tpp047 copies/ml was detected and mean half-life for clearance (t½ clearance) was 7.89 hours (range 5.34). Blood RNA: Mean peak-level 8829(range 20366) 16SrRNA copies/ml blood; (t½ clearance) 5.24 hours (range 0.78). Ulcer DNA 1.14 × 10 5 copies/strip and RNA 4.35 × 10 7 copies/strip with a t½ (clearance) of 1.67 and 3.76 hours, respectively. T. pallidum nucleic acids were undetectable in all samples after 56 hours. All patients had serology consistent with disease stage at baseline and cure at one month. Conclusions: T. pallidum qPCR presents a novel and quick way of monitoring early syphilis treatment efficacy. Both DNA and RNA may be suitable targets to measure bacterial clearance from blood and ulcer exudates. Ulcers may be non-infectious as soon as 56 hours post-treatment.